Neural decoding of single vowels during covert articulation using electrocorticography - Ikeda, Shigeyuki; Shibata, Tomohiro; Nakano, Naoki; Okada, Rieko; Tsuyuguchi, Naohiro; Ikeda, Kazushi; Kato, Amami (Frontiers in Human Neuroscience, 2014)
The human brain has important abilities for manipulating phonemes, the basic building blocks of speech; these abilities represent phonological processing. Previous studies have shown change in the activation levels of broad cortical areas such as the premotor cortex, the inferior frontal gyrus, and the superior temporal gyrus during phonological processing. However, whether these areas actually convey signals to representations related to individual phonemes remains unclear. This study focused on single vowels and investigated cortical areas important for representing single vowels using electrocorticography (ECoG) during covert articulation. To identify such cortical areas, we used a neural decoding approach in which machine learning models identify vowels. A decoding model was trained on the ECoG signals from individual electrodes placed on the subjects’ cortices. We then statistically evaluated whether each decoding model showed accurate identification of vowels, and we found cortical areas such as the premotor cortex and the superior temporal gyrus. These cortical areas were consistent with previous findings. On the other hand, no electrodes over Broca’s area showed significant decoding accuracies. This was inconsistent with findings from a previous study showing that vowels within the phonemic sequence of words can be decoded using ECoG signals from Broca’s area. Our results therefore suggest that Broca’s area is involved in the processing of vowels within phonemic sequences, but not in the processing of single vowels.